Natural enemies of mealybugs (Hemiptera: Coccomorpha: Pseudococcidae and Putoidae) associated with coffee roots in Colombia - Gil, Zulma Nancy; Constantino, Luis Miguel; Benavides Machado, Pablo (Revista Colombiana de Entomología, 2023)
Some species of Pseudococcidae and Putoidae (Hemiptera: Coccomorpha) are important pests of coffee roots in many parts of the world, for their management the biological control is an alternative; therefore, a search and identification of natural enemies of mealybugs attacking coffee roots in Colombia were carried out in eight coffee producing departments. Mealybug samples from 520 farm sites were collected, fixed in alcohol, cleaned, sorted, and separated by color and size. 120 specimens of natural enemies were found in 44 farm sites parasitizing mealybugs of the families Putoidae and Pseudococcidae. Caldas department presented the highest percentage of farm sites with parasitoids with 15.3%, followed by Antioquia with 14.1%, Cauca with 13.8, Valle del Cauca with 10.4%, Tolima with 4.2%, Risaralda with 3.8%, and finally Quindío with 1.2%. Subsequently, 20 of the farm sites in which parasitism was detected were visited again and mealybugs were collected and transported alive to the laboratory. From the scale insects kept in the rearing chambers 28 adult parasitoid wasps, i.e. Aenasius caeruleus Brues, 1910, Aenasius bolowi Mercet, 1947, Aenasius tachigaliae (Brues, 1922), Aenasius af. mitchellae Noyes and Ren, 1995, Zarhopalus putophilus Bennett, 1957, Hambletonia pseudococcina Compere, 1936, Hambletonia sp., Prochiloneurus af. dactylopii (Howard, 1885), Leptomastix sp., Cicoencyrtus sp. (Hymenoptera: Encyrtidae) and five adult cecidomyid: (Diptera Cecidomyiidae) emerged. Two species of coccinellids (Coleoptera: Coccinellidae) and an antagonistic fungus Trichoderma sp. were also recorded. From these findings, it is concluded that there are several species of natural enemies that are naturally controlling mealybugs that infest coffee roots. It is necessary to explore an augmentation biological control approach.